2015
DOI: 10.5539/jas.v7n11p1
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stage Affects Dose Response of Selected Glyphosate-Resistant Weeds to Premix of 2,4-D Choline and Glyphosate (Enlist Duo™ Herbicide*)

Abstract: With the intent to control glyphosate-resistant and hard to control weeds, a formulation of 2,4-D choline (24.4%) and glyphosate (22.1%) (Enlist Duo™ herbicide) (Note 1) has been developed recently to be used post-emergence in corn and soybean tolerant to Enlist Duo™ in the United States. Dose response studies were conducted under greenhouse conditions for the evaluation of effective rates of Enlist Duo™ to control glyphosate-resistant common waterhemp (Amaranths rudis Sauer), giant ragweed (Ambrosia trifida L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…In glasshouse studies, Chahal et al . () and Ganie et al . () reported that A. trifida control declined and higher herbicide rates were needed for effective control at 20 cm height compared with 10 cm height following application of 2,4‐D choline plus glyphosate and fluthiacet‐methyl plus mesotrione respectively.…”
Section: Discussionmentioning
confidence: 93%
“…In glasshouse studies, Chahal et al . () and Ganie et al . () reported that A. trifida control declined and higher herbicide rates were needed for effective control at 20 cm height compared with 10 cm height following application of 2,4‐D choline plus glyphosate and fluthiacet‐methyl plus mesotrione respectively.…”
Section: Discussionmentioning
confidence: 93%
“…scoparia was first identified in Kansas [7] and has now been identified in multiple Great Plains States including Colorado, South Dakota, North Dakota [8], Montana [9], Nebraska [10], and in the Canadian provinces of Alberta [11], Saskatchewan and Manitoba [12]. Most of the reported GR K .…”
Section: Introductionmentioning
confidence: 99%
“…Wats.] have been confirmed resistant to glyphosate (Chahal et al, 2015a;. The occurrence of GR weeds is a serious concern, particularly for midwestern soybean growers, because of limited effective POST herbicide options.…”
Section: Introductionmentioning
confidence: 99%